The Cardiac Pacemaker Story—Fundamental Role of the Na+/Ca2+ Exchanger in Spontaneous Automaticity - Kohajda, Zsófia; Loewe, Axel; Tóth, Noémi; Varró, András; Nagy, Norbert (Frontiers in Pharmacology, 2020)
The electrophysiological mechanism of the sinus node automaticity was previously considered exclusively regulated by the so-called “funny current”. However, parallel investigations increasingly emphasized the importance of the Ca2+-homeostasis and Na+/Ca2+ exchanger (NCX). Recently, increasing experimental evidence, as well as insight through mechanistic in silico modeling demonstrates the crucial role of the exchanger in sinus node pacemaking. NCX had a key role in the exciting story of discovery of sinus node pacemaking mechanisms, which recently settled with a consensus on the coupled-clock mechanism after decades of debate. This review focuses on the role of the Na+/Ca2+ exchanger from the early results and concepts to recent advances and attempts to give a balanced summary of the characteristics of the local, spontaneous, and rhythmic Ca2+ releases, the molecular control of the NCX and its role in the fight-or-flight response. Transgenic animal models and pharmacological manipulation of intracellular Ca2+ concentration and/or NCX demonstrate the pivotal function of the exchanger in sinus node automaticity. We also highlight where specific hypotheses regarding NCX function have been derived from computational modeling and require experimental validation. Nonselectivity of NCX inhibitors and the complex interplay of processes involved in Ca2+ handling render the design and interpretation of these experiments challenging.